Effect of tax avoidance and capital structure on firm value with managerial ownership as a moderating variable - Hapsari, RR. Prima Dita; Herianto, Yuli; Theodora, Paula (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
The phenomenon of tax avoidance is a concern for stakeholders. Therefore, this study examines the influence of tax avoidance and capital structure on firm value, with managerial ownership as a moderating variable. The sample used in this study comprised a manufacturing company in the consumer goods subsector, listed on the IDX, for the 2018-2024 period, employing purposive sampling. This study employed panel data regression to test the hypotheses in EViews. The results indicate that tax avoidance has a positive effect on firm value; capital structure has a positive effect on firm value; managerial ownership has positive effects on both tax avoidance and firm value; and managerial ownership has positive effects on capital structure and firm value. The practical implications of this research are to encourage companies to manage taxes efficiently and in accordance with regulations, align debt use with operational capacity, and utilize managerial share ownership as an internal strategy to increase accountability in decision-making